GROWTH HORMONE TREATMENT OF CHILDREN WITH SHORT STATURE LIVED IN SAMARA REGION - E.G. Mikhailova; T.I. Kaganova; O.V. Kuchumova (Вопросы современной педиатрии, 2009)
Growth inhibition in children is heterogeneous state, and it may accompany many endocrine, somatic, genetic and chromosome diseases. Generally recognized medications for treatment of somatotropic insufficiency in present times are biosynthetic analogs of human growth hormone (hGH), obtained with DNA-recombinant technology. This article presents the results of estimation of effectiveness of hGH in treatment of children with short stature (n=77) with isolated deficiency of growth hormone, panhypopituitarism, Turner's syndrome, treated with hGH during 3 years. All patients had significant positive dynamics of clinical status, the velocity of grouth increased from 1.9 cm (initial) per year to 11.0 cm (the end of first year), with following decrease to 5.3 cm per year. SDS index of growth had stable tendency to increase: medium SDS index of growth initially was -3.9 SD, on the end of third year – -2.0 SD. It was shown, that treatment with hGH is effective in any types of short stature. Key words: children, short stature, treatment, human growth hormone. (Voprosy sovremennoi pediatrii — Current Pediatrics. 2009;8(1):108-113)